Partners in Sickness and in Health? Relationship-Centered Veterinary Care and Self-Educated Pet Owners in Germany: A Structural Equation Model - Küeper, Alina M.; Merle, Roswitha (Frontiers in Veterinary Science, 2021)
In recent years, the web has become a widely used source for health information. Pet owners seem to respond to the supply of medical information on the Internet by increasing their self-education. However, after more than a decade of the digital revolution, little is known about the Internet’s impact on the veterinarian-pet owner relationship. Recent research has raised concerns regarding the increase in self-education among pet owners. However, reasons suggest that the Internet might be a valuable source of pet-owner education for veterinarians. In particular, relationship-centered approaches of care might benefit from the information provided. Our study aimed to determine the perception of German veterinarians with regard to pet owners’ self-education on different aspects of veterinary care. An online survey was conducted for German veterinarians from November 2016 to June 2017. Data were analyzed using exploratory factor analysis and structural equation modeling. Within the structural equation model, we evaluated how the veterinarians’ attitude toward relationship-centered care might affect the evaluation of pet owners’ self-education. A total of 585 valid questionnaires were completed. The majority of veterinarians (83.6%) welcomed the principles of shared decision-making. Practically, all veterinarians reported a noticeable increase in pet owners’ self-education within the last few years. Perceptions on self-education’s impacts on veterinary practice varied among the participants. A beneficial impact of self-education was reported regarding the general quality of veterinary care and quality of follow-up care. Most concerns were related to a negative impact on the veterinarian-pet owner relationship and the pet owners’ demands on the veterinarians’ work after self-education. Moreover, many participants were afraid that unfiltered information may unsettle pet owners and, therefore, advised them against self-education. The structural equation model confirmed the hypothesis that a veterinarian’s positive attitude towards shared decision-making, empathic behavior, and his/her evaluation of self-education were associated. Therefore, we concluded that while there are beneficial potentials, there seem to be barriers that prevent the effective use of the Internet as a supportive medium in veterinary care. Further research and training are needed to enable the use of the Internet as an ancillary medium.